Implementation of Quran Recitation Guidance as an Effort to Tahsin Quran Recitation with Tajwid for Children in Temiyang Village, Kroya District, Indramayu Regency - Sri Eni; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
The aim of this research is to introduce the science of tajwid and makhorijul letters correctly. aims to provide learning about the science of recitation and how to read the Al-Qur'an tartil and fluently to children in Temiyang village. Makhorijul itself is a pronunciation that covers the places where the sounds of the hijaiyah letters come out. Reading the Al-Qur’an is a good practice. Before reading the Al-Quran, we must understand tajwid and makhraj first so that when we read the Al-Quran fluently, well and correctly. The method used in implementing the Al-Qur’an tutoring program is by reciting the Al-Qur’an together and then reciting the Al-Qur’an one by one. And the method used in carrying out learning recitation and makhorijul letters is the lecture, demonstration and question and answer method. The number of children who recite the Al-Qur’an is 40 and there is a shortage of workers, namely 2 Al-Qur’an teachers. Children who recite the Al-Qur’an at Upik's mother's house experience a lack of insight and knowledge about the hijaiyah letters and tajwid. The approach method used in activities during KKN is learning to recite the Al-Qur’an with good and correct Tajwid letters. This is done because it is one of the effective ways because you can listen directly and check your understanding and correct the pronunciation of the hijaiyah letters. With this guidance, students can also get closer to their partners. Based on the results of the KKN, it can be concluded that there is an increase in knowledge in children at Mrs. Upik's residence about reciting the Al-Qur’an with Tajwid letters properly and correctly, and helping Al-Qur’an teachers to increase their insight in reading Al-Quran.